Behavioral Impediments to Valuing Annuities: Complexity and Choice Bracketing - Jeffrey R. Brown; Arie Kapteyn; Erzo F.P. Luttmer; Olivia S. Mitchell; Anya Samek (Institute of Labor Economics (IZA), 2019)
This paper examines two behavioral factors that diminish people's ability to value a life-time income stream or annuity, drawing on a survey of about 4,000 adults in a U.S. nationally representative sample. By experimentally varying the degree of complexity, we provide the first causal evidence that increasing the complexity of the annuity choice reduces respondents' ability to value the annuity, measured by the difference between the sell and buy values people assign to the annuity. We also find that people's ability to value an annuity increases when we experimentally induce them to think jointly about the annuitization decision as well as how quickly or slowly to spend down assets in retirement. Accordingly, we conclude that narrow choice bracketing is an impediment to annuitization, yet this impediment can be mitigated with a relatively straightforward intervention.
Keywords: D14; D91; G11; H55; 330; pension; annuity; retirement income; Social Security; cognition; behavioral